The Influence of Qard and Zakat on Profitability of Islamic Banks in Indonesia - Ines Nathasia Oktaviani; Salim Alaidrus; Siswanto Siswanto (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
The aims of this research was to find out the influence of qardh and zakat on profitability (ROA) of Islamic banks in Indonesia. The population in this research is Islamic banks that registered in Bank Indonesia from 2016 to 2020, sample withdrawal by using purposive sampling techniques, and obtained 4 Islamic banks that meet the criteria. This research uses a statistical test of MRA (Multivariate Regression Analysis) with the following results: qardh variable has a tcount = -4.788 and a ttable = 2.10982 (tcount > ttable) with a significance level 0.0002 < 0.05. Thus H1 is accepted, qardh has a significant negative effect on profitability of Islamic bank, which means that the greater qardh that has been channeled to the community, the profitability of Islamic banks will decrease. The zakat variable has a tcount = 4.008 and a ttable = 2.10982 (tcount > ttable) with a significance level 0.001 < 0.05. Thus H2 is accepted, zakat has a significant positive effect on profitability of Islamic banks, which means that the greater zakat that has been channeled to the community, the profitability of Islamic banks will increase.